1994
DOI: 10.1111/j.1752-0606.1994.tb01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There More to Counting Than What Meets the Eye? Comment on Snyder and Rice

Abstract: Snyder and Rice (1994) comment that Shortz, Worthington, McCullough, DeVries, andMorrow (1994) failed to use sophisticated methods in their identijlcation of prolific authors, institutions, andjournals within the field of mari-tal therapy. This article is a response to Snyder and Rice. We argue that Snyder and Rice's suggested methods emphasize a diferent research question than our original question. We investigatedproductivity of authors and institutions, not im-pact of scholars on the field of marital thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…We also agree with Gurman that "this analysis may be more informative about the three journals surveyed here than about family therapy as a whole" (Gurman, 1981, p. 86). The importance and representativeness of these original and major outlets of MFT scholarship is, however, supported by recent analyses by Snyder and Rice (1994) and Shortz, Worthington, McCollough, Kurusu et al (1994). In the latter study, for example, a survey of 38 marriage and family therapy experts found that JMFT, FP, and AJFT ranked first, second, and fifth most prominent, respectively, among a list of 16 journals in the field.…”
Section: Discussionmentioning
confidence: 86%
“…We also agree with Gurman that "this analysis may be more informative about the three journals surveyed here than about family therapy as a whole" (Gurman, 1981, p. 86). The importance and representativeness of these original and major outlets of MFT scholarship is, however, supported by recent analyses by Snyder and Rice (1994) and Shortz, Worthington, McCollough, Kurusu et al (1994). In the latter study, for example, a survey of 38 marriage and family therapy experts found that JMFT, FP, and AJFT ranked first, second, and fifth most prominent, respectively, among a list of 16 journals in the field.…”
Section: Discussionmentioning
confidence: 86%
“…They suggested two alternative methods of assessing journals' influence, utilizing the citation patterns noted in Social Sciences Citation Index and surveying a sample of experts in the field. Shortz Worthington, McCullough, Kurusu, Bryant, and DeVries (1994) replied by demonstrating that the results obtained from Snyder and Rice's methodology did not differ appreciably from their original results.…”
Section: Methodsmentioning
confidence: 94%
“…Finally, on a more practical level, although there have been various mathematical methods suggested for quantifying authorship order, they have been generally shown to yield results that differ very little (if at all) from the fractional counting approach developed by Lindsey (1980) and used in our analysis. See, for example, Shortz et al (1994) and Cox and Blount (1989) for comparisons of the Lindsey (1980) approach with a method for proportionally weighing authorship order developed by Howard, Cole, and Maxwell (1987). In this latter method, an author in ordinal position i + 1 always receives 50% of the authorship credit assigned to the author immediately preceding him or her (i.e., 50% of the credit assigned to author i).…”
Section: Sample Of Editorial Board Membersmentioning
confidence: 99%